Economic Pressures and Occupational Health and Safety: A Qualitative Study of Workers’ Experiences in the Shipbuilding and Ship Scrapping Industry in Kendari - Dwianto, Ikhsan; Mokodompit, Eliyanti Agus (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
The shipbuilding and ship scrapping industries play a significant role in maritime economic development, especially in coastal areas such as Kendari. Within the framework of industrial economics theory, this sector reveals the complex relationship between cost-efficiency, market structure, and its influence on occupational health and safety (OHS) standards. This research endeavor aims to investigate the correlation between economic constraints in the shipbuilding and ship dismantling sectors and the prevalence of significant occupational hazards, as well as their impact on the accessibility of occupational health services in Kendari. A descriptive qualitative approach was employed, utilizing an intrinsic case study design. Data were gathered through comprehensive interviews with a cohort of 12 pivotal informants, comprising both laborers and proprietors of ship workshops, as well as direct observational analysis conducted at the workplace. The findings reveal that cost-efficiency pressures drive the neglect of occupational health and safety (OHS) practices. The majority of workers do not use personal protective equipment (PPE), have never participated in OHS training, and work in unsafe environmental conditions. Common health complaints include respiratory issues, skin irritation, fatigue, and hearing impairment. Access to occupational health services is also highly limited, with most workers lacking social security and relying on self-medication. This study concludes that the economic structure of the industry directly contributes to the lack of adequate workplace safety measures. Therefore, an inclusive, participatory, and community-based policy approach is essential for improving OHS protections in the informal sector.